Baltic Coast. A new architecture for the Baltic Coast, Mecklenburg-Vorpommern. - (:unkn) unknown (My University, 2017)
Für Mecklenburg-Vorpommern wird, nicht zuletzt vor dem Hintergrund internationaler Krisen, ein Anwachsen des Fremdenverkehrs erwartet. Mit dem Fokus auf die Ostseeküste wird in der Publikation der Frage nachgegangen, wie dieser "Hype" in strategische Impulse für die Stadt- und Regionalentwicklung umgesetzt werden kann und was diese Entwicklung für die Küstenstädte bedeutet. Das Projekt Baltic Coast thematisiert städtebauliche Strategien und architektonische Konzepte, die auf Veränderungen reagieren und die Gestaltung von Trends selbst beeinflussen.

Mecklenburg-Vorpommern with 1700 km of coast in 2016 has been the national Wunderland of tourism, for 2017 a further rise is expected, not as last because of international insecurities and risks. Focused on the Baltic sea coast, the master design studio aims at a double and connected question: How can a possibly short-term Baltic hype be transformed into strategic impulses for urban and regional development? How does in this transformation of the coast change architectural practices and paradigms in leisure and tourism, and what are their impulses towards and interferences with other sectors? The Baltic Coast project addresses urbanistic strategies and architectural concepts that react towards changes and that influence the shaping of trends themselves. The methodological steps are oriented towards a design-based knowledge production, starting with an exploration spatial and socio-economic context and field surveys, connected to proceeding urban and architectural design research in territorial, local and object scales, combined with presentations, debates, poster and mode) drawing.
Keywords: Küstengebiet; Regionalentwicklung; Fremdenverkehr; Standortfaktor; Stadtentwicklung; Dorfentwicklung; Bebauung; Architektur; Siedlungsplanung; Siedlungsstruktur; Seebad; Tourismus; Bäderarchitektur; Regionalstruktur; Transformation